2017
DOI: 10.1136/bmjopen-2016-013966
|View full text |Cite
|
Sign up to set email alerts
|

Is postoperative decrease of serum albumin an early predictor of complications after major abdominal surgery? A prospective cohort study in a European centre

Abstract: ObjectiveTo test postoperative serum albumin drop (ΔAlb) as a marker of surgical stress response and early predictor of clinical outcomes.DesignProspective cohort study (NCT02356484). Albumin was prospectively measured in 138 patients undergoing major abdominal surgery. Blood samples were collected before surgery and on postoperative days 0, 1 2 and 3. ΔAlb was compared to the modified estimation of physiologic ability and surgical stress (mE-PASS) score and correlated to the performances of C reactive protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
90
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 33 publications
6
90
3
4
Order By: Relevance
“…This is different from previously published data, where a 20–35% drop was observed [12, 13]. In these studies, however, the greatest decrease in albumin level was observed in patients undergoing liver surgery [19].…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…This is different from previously published data, where a 20–35% drop was observed [12, 13]. In these studies, however, the greatest decrease in albumin level was observed in patients undergoing liver surgery [19].…”
Section: Discussioncontrasting
confidence: 90%
“…Relatively few publications analysed it as a potential marker of early adverse events, and therefore it is seldom used as a biomarker of complications [12, 13, 19, 20]. However, albumin, which is considered a negative acute phase protein with a half-life of 20 days, seems to have perfect characteristics for a useful biomarker [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of PTH response indicates that calcium in conjunction with other factors may blunt the normal PTH response. Calcium is a known regulator of 1‐alpha hydroxylase activity and PTH secretion . Albumin corrected calcium increased significantly after surgery and could theoretically augment the observed 35% decrease in serum 1,25(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Injury or trauma induces a series of metabolic, inflammatory, and endocrine changes known as the “surgical stress response.” A particular and abrupt event in response to surgery is a profound change in the distribution of proteins between the intra‐ and extravascular compartments . This redistribution gives rise to an instant reduction in the concentration of most circulating proteins, which necessitates immediate changes in factors dependent on protein binding in serum, for instance, calcium and steroid hormones …”
Section: Introductionmentioning
confidence: 99%